From People to Objects: The digital transformation of fields. Issue 7 (July 2022) - Alaimo, Cristina
Digital technologies are reconfiguring organizations and their environments. Activities are increasingly distributed across fields and coordinated by data, algorithms and machines. This paper investigates data objects (objects made of data structured and aggregated under a specific template) and their role in structuring fields and field practices. It studies programmatic advertising, an automated bidding process with hundreds of participants, whereby media spaces are auctioned in real time as individual users browse online content. To work on such a large scale, programmatic advertising must standardize existing field knowledge into data and coordinate collective action through objects, algorithms and technologies. This study shows how data, data objects and their infrastructures are involved in transforming the links between institutions and practice. The makeup and functioning of data and data objects reorient existing cognitive, normative and regulative structures, constrain the rule of engagement of actors and enable field-level autonomous interaction. The datafication of knowledge and automation of practices exposed in this paper call for a thorough rethinking of existing approaches to the concepts of organizations and fields.